THE DEVELOPMENT OF FLIP BOOK-BASED E-MODULE ON THE SUBJECT OF COMPUTER AIDED MANUFACTURING (CAM) - Muhammad Hudan Rahmat; Harie Satiyadi Jaya (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2020)
This study aims to developed a flipbook-based e-module in Computer Aided Manufacturing (CAM) course, because e-modules are considered to have the advantage of being innovative, displaying complete teaching materials, interesting, interactive, and being able to carry out the cognitive functions of students well. The e-module development stage adapted the modified Dick & Carey model into four stages, namely (1) needs analysis, (2) product design, (3) validation and evaluation, and (4) product revision. Based on the development results obtained the following data; (1) the lecturer assessment of the e-module showed that the product has